Najdawniejsze zapiski z księgi miejskiej Pleszewa (1428-1444). Wyd. Tomasz Jurek, 2011 - Adam Kozak (Czasopismo Prawno-Historyczne)
Najdawniejsze zapiski z księgi miejskiej Pleszewa (1428-1444). Wyd. Tomasz Jurek, 2011